Development of mechanistic flexible pavement design method for Malaysian conditions / Ahmad Kamil Arshad - Arshad, Ahmad Kamil (2009)
Malaysia currently utilises an empirically-based pavement design procedure which is adopted from the AASHTO 1972 Design Guide. Elsewhere, pavement design approach is shifting towards mechanistic-based procedures that are based on the mechanics of materials. The purpose of this study is to develop a framework for mechanistic design of flexible pavement suitable for Malaysian conditions. In this study, resilient modulus characterisation of flexible pavement materials (asphaltic concrete wearing and binder course, base and sub-base) used in Malaysia, according to the Public Works Department of Malaysia's (PWD) Specification for Road Works (JKR/SPJ/1988), were carried out so that these can be used as inputs into a mechanistic-based procedure. Granite-type aggregates were used as it is produced by most quarries in Malaysia, and it is representative of the flexible pavement materials locally used. The repeated load indirect tensile test method (ASTM D4123-82) was used to investigate the effects of variations at different temperatures, gradation, bitumen content and penetration type and to determine the resilient modulus values of asphaltic concrete (ACW20 and ACB 28). Regression models of ACW20 and ACB28 were developed and recommended for use as predictive models. Base (Type II) and sub-base (Type E) were tested at different gradations and moisture contents using the repeated load triaxial test in accordance with AASHTO T3 07-99. From the test, the k-9 constitutive model was used to characterise the base and sub-base materials. Field work data derived from the Falling Weight Deflectometer tests were compared to the values obtained from laboratory testing of asphaltic concrete, base and sub-base materials and were found to be consistent for those sites where the thickness of the pavement materials were consistent and uniformly layered.